(untitled) (Damascus University Journal of agriculture sciences, 2021)
This research was carried out on a farm in Abe Jerash College of Agriculture at the University of Damascus during the growing season 2014-2015 to evaluate the effect of water stress on vine plant by using three Water treatments: T1: full irrigation )100% of required amount of irrigation water), and T2: (70% of full irrigation), and T3: (60% of full irrigation). Water use efficiency in both treatments (T2) and (T3) was the highest, as it increased by 35% of (T1). Yield in (T1) was the highest with 17.65 ton ha-1, whereas yield decreased in both (T2) and (T3) by 4.6% and 16.4% respectively of (T1), and there were no significant differences between the three treatments. Response factor to deficit irrigation (ky) was 0.18, 0.97 in (T2) and (T3) respectively of (T1). It means that vine response to deficit irrigation.